2001
DOI: 10.3138/cmlr.57.3.377
|View full text |Cite
|
Sign up to set email alerts
|

Interlanguage Development of Spanish Learners: Comprehension, Production, and Interaction

Abstract: This study explores the relationship between group interaction and interlanguage development, specifically listening comprehension and the production of target grammar forms. Two groups (39 participants in total) of first-semester Spanish students at an American university took notes on a mini-lecture, then completed a text reconstruction and listening comprehension test. The experimental group (n = 18) interactively shared notes for five minutes in small groups; the control group (n = 21) did not interact, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Even though results from the Storch (1999) and Garcia and Asención (2001) studies provided partial support for the benefits of collaborative tasks, Kuiken and Vedder (2002) reported contrary findings. They employed a pretest–posttest design to explore whether collaborative and individual tasks facilitated the acquisition of the passive form by 34 Dutch high school learners.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Even though results from the Storch (1999) and Garcia and Asención (2001) studies provided partial support for the benefits of collaborative tasks, Kuiken and Vedder (2002) reported contrary findings. They employed a pretest–posttest design to explore whether collaborative and individual tasks facilitated the acquisition of the passive form by 34 Dutch high school learners.…”
mentioning
confidence: 93%
“…As Williams (2001) noted, without a control group (i.e., learners who complete an individual task), the relationship between the test results and the collaborative tasks is still in need of further investigation. Studies to date that have compared individual and collaborative task performance (Garcia & Asención, 2001; Kuiken & Vedder, 2002; Storch, 1999) have focused on the acquisition of grammar features, quality of students' writing samples, or listening comprehension.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One reason can be that both groups received the same amount of time (i.e. thirty minutes) in performing the tasks while in previous studies (Storch, 1999;Garcia & Asencion, 2001) pair groups had more time than individual groups. Another reason might be related to the nature of the interaction that took place during pair work.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies reported the effective role of collaboration on various aspects of second language learning (Lapkin, Swain & Smith, 2002 Storch, 1999Storch, , 2005. Among them, Storch (1999) and Garcia and Asencion (2001) supported partially the benefits of collaborative tasks. Therefore, due to scarcity of studies conducted on the comparison of collaborative versus individual output tasks, this study also aims to fill this gap by comparing two groups of learners working on the enhanced text and editing task in collaboration and individually.…”
Section: Introductionmentioning
confidence: 99%